2016
DOI: 10.1016/j.cplett.2016.04.078
|View full text |Cite
|
Sign up to set email alerts
|

New insights into electrocatalytic ozone generation via splitting of water over PbO2 electrode: A DFT study

Abstract: The viable mechanisms for O 3 generation via the electrocatalytic splitting of H 2 O over β-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…The reaction is found to occur via a Langmuir-Hinshelwood mechanism where two species adsorb to the surface (O 2 and O), the diffuse across the surface interacting with each other before desorbing as a molecule (O 3 ). This is interesting as the same mechanism run on β-PbO 2 previously 23 , showed that the formation of O 3 preferred to occur via an Eley-Rideal mechanism where the O 2 passes over the surface and interact with an adsorbed species forming O 3 and desorbing. This shows that although the formation of O 3 occurs via the same reaction step, the chemistry of each catalyst is not necessarily the same, and thus this could have an overall effect of the CE of O 3 as a result.…”
Section: Final State Of Reaction (Fs)mentioning
confidence: 85%
“…The reaction is found to occur via a Langmuir-Hinshelwood mechanism where two species adsorb to the surface (O 2 and O), the diffuse across the surface interacting with each other before desorbing as a molecule (O 3 ). This is interesting as the same mechanism run on β-PbO 2 previously 23 , showed that the formation of O 3 preferred to occur via an Eley-Rideal mechanism where the O 2 passes over the surface and interact with an adsorbed species forming O 3 and desorbing. This shows that although the formation of O 3 occurs via the same reaction step, the chemistry of each catalyst is not necessarily the same, and thus this could have an overall effect of the CE of O 3 as a result.…”
Section: Final State Of Reaction (Fs)mentioning
confidence: 85%
“…In contrast to the orthorhombic α-phase of PbO 2 , the β-crystallographic phase is known to possess a much better conductivity for ozone generation. 25 These in situ-loaded β-PbO 2 presents a well-defined and cuboid-faceted morphology, and distribute uniformly on the maintained bulk porous Pb matrix (Figure 3b), which makes the argenteous BPP to be black-brown-coated (Figure 3c). From the selected area electron diffraction (SAED) pattern (Figure 3d), the β-PbO 2 cuboids are revealed to be well-defined single-crystalline particles, with no undesirable amorphous layer on the surface, which is evidently confirmed by their clear crystalline edge observed in the high-resolution transmission electron microscopy (HRTEM) image (Figure 3e).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, an unspecified broad plasmon peak at around 50 eV can be detected in the low-loss electron energy loss spectrum (EELS) of the β-PbO 2 cuboids (Figure 3f), confirming a nonextrinsic collective electron oscillation at high frequency in the defective crystals, which indicates the presence of highdensity oxygen vacancies in the as-synthesized β-PbO 2 . Such an oxygen vacancy-rich nonstoichiometric PbO 2 obtained from the in situ anodic oxidation will benefit the electron conduction and oxygen molecule adsorption, 25 which favors the EOP with high current efficiency. 2.2.…”
Section: Resultsmentioning
confidence: 99%
“…Lead oxide performed as an anode material for the potential application in wastewater treatment . It is reported that the nanosized lead oxide particles may act as anticancer and antimicrobial drugs. , A theoretical mechanism has been predicted for the formation of ozone through the electrocatalytic splitting of water over PbO 2 catalyst …”
Section: Introductionmentioning
confidence: 99%
“…11,12 A theoretical mechanism has been predicted for the formation of ozone through the electrocatalytic splitting of water over PbO 2 catalyst. 13 With the progress of research on modern material science, the synthesis of nanomaterials is an important step due to their high surface to volume ratio that contributes to the exceptional catalytic, optical, electronic, and magnetic properties. Several techniques, such as chemical, 14 sonochemical, 15 sol−gel, 16 solvothermal, 17 thermal decomposition, 18 and microwave irradiation, 19 have been reported in the literature for the synthesis of lead oxide nanoparticles.…”
Section: ■ Introductionmentioning
confidence: 99%